Model of Accounting Digitalization Readiness in MSMEs: An Empirical Study of Technological Literacy, Internal Control, and Performance - Syahputri, Deandra Fakhira; Putu, Nadira Lestari (Universitas Sains dan Teknologi Komputer, 2025)
The digital technology progression has brought about a revolution in the global accounting systems and change within the MSME sector of Indonesia. Though they play a significant role in national GDP, digital accounting technology acceptance by MSMEs is still scanty, which is attributed to their low-tech knowledge and lack of effective internal controls. The present research aims to develop an empirical model of MSMEs’ digital accounting readiness by analyzing the impact of technological literacy and the degree of internal control effectiveness on business performance. A qualitative explanatory method was applied through a survey of 200 MSME players from DKI Jakarta, West Java, and Central Java. The data were processed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The outcomes indicate that all interactions among the variables are significant: technological literacy (β = 0.43) and internal control (β = 0.37) positively impact readiness for digital adoption, while, in turn, digitalization readiness (β = 0.45) positively impacts MSME performance. The model has a strong predictive power (R² > 0.50). The integration of the Technology Readiness and Adoption Theory with the Accounting Information System Theory, by including internal control as a dimension of digital governance, is the main contribution of this study. From a practical standpoint, the outcomes provide strategic recommendations to enhance technological literacy and introduce a risk-based control system to accelerate MSME digital transformation in Indonesia.